Adalimumab Induced Subcutaneous Nodular Sarcoidosis; A Rare Side Effect of Tumor Necrosis Factor-α Inhibitor - Au, Sonoa; Mirsaeidi, Mehdi; Aronson, Iris K; Sweiss, Nadera J. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2014)
Adalimumab and other tumor necrosis factor-α inhibitors have been shown in the recent years to successfully treat sarcoidosis refractory to systemic corticosteroids and other agents.  However, there have been an increasing number of cases of sarcoidosis paradoxically induced by these agents.  It is hypothesized that this is due to the disruption of the fine balance of cytokines involved in granuloma formation. We describe the first case of adalimumab-induced subcutaneous nodular sarcoidosis in a patient with pulmonary sarcoidosis.